2001
DOI: 10.1111/j.1095-8649.2001.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of the sperm of the Japanese bitterling

Abstract: Sperm of the Japanese bitterling Tanakia limbata that had been cryopreserved with 5 or 10% methanol plus 95 or 90% foetal bovine serum (FBS) showed higher percentage and longer duration of motility than those that had been cryopreserved with 90% FBS and 10% DMSO, glycerol, N,N-dimethylacetamide or N,N-dimethylformamide. Foetal bovine serum, used as extender, had some cryoprotective effects when spermatozoa were cooled either with 10% methanol or without methanol. Spermatozoa, cooled to 40 C and then immersed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Several studies have shown FBS to be an excellent cryopreservation diluent (Aoki et al , 1997; Ohta et al , 2001; Tsutaka et al , 2006). In the present study, no conspicuous differences in post‐thaw motility were found between ASP and FBS when 10% MeOH was used as a cryoprotectant.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown FBS to be an excellent cryopreservation diluent (Aoki et al , 1997; Ohta et al , 2001; Tsutaka et al , 2006). In the present study, no conspicuous differences in post‐thaw motility were found between ASP and FBS when 10% MeOH was used as a cryoprotectant.…”
Section: Discussionmentioning
confidence: 99%
“…Optimum cooling rates for spermatozoa vary among species; for example, from −5 to −15° C min −1 in the oily bitterling Tanakia limbata (Temminck & Schlegel) (Ohta et al , 2001), −40° C min −1 in the Colorado pikeminnow Ptychocheilus lucius Girard (Tiersch et al , 2004) and −42·5° C min –1 in the ayu Plecoglossus altivelis altivelis (Temminck & Schlegel) (Tsutaka et al , 2006). Tiersch (2001) recommended a cooling rate of −40° C min –1 for sperm cryopreservation in a broad range of species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations